THE ROLE OF NURSING IN ORGANIZING THE REHABILITATION PROCESS AFTER STROKE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Stroke is one of the leading diseases that cause disability and death, and restoring the functional status of patients in the post-stroke period is of great importance. Nursing care plays an important role in the effective organization of the post-stroke rehabilitation process, playing a leading role in patient care, monitoring the condition, preventing complications, and implementing rehabilitation measures.
Keywords: Stroke, rehabilitation care, nursing care